FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MUDHARABAH PADA BANK UMUM SYARIAH - Istining Amelia Nursafitri; Suryani Sri Lestari; Vita Arumsari (Politeknik Negeri Semarang, 2023)
Abstrak: This study aims to analyze the significance of the effects of the factors of TPF, CARa, NPFa, and FDRa that influence on Mudharabah Financing of Islamic Commercial Banks for the 2018-2021 Period, either simultaneously or partially. The population of this study is all Islamic Commercial Banks in Indonesia totaling 12 BUS, while the sample in this study was selected using purposive sampling technique resulted in 6 (six) BUS that meet the criteria, including Bank Muamalat Indonesia, Bank Victoria Syariah, Bank BJB Syariah, Bank Panin Dubai Syariah, Bank Bukopin Syariah, and Bank BCA Syariah. The analysis model in this study uses the Multiple Linear Regression Analysis Model. The analysis technique uses the F test, the coefficient of determination test (R2), and the t test which is processed using the SPSS 25.00 program. The results of proving the hypothesis and the discussion in this study show that TPF, CAR, NPF, and FDR simultaneously have a significant effect on Mudharabah Financing for Islamic Commercial Banks for the 2018-2021 Period. While the results of the partial analysis show that TPF, CAR, and FDR each have a positive and significant effect on Mudharabah Financing. While the NPF partially has a negative and significant effect on Mudharabah Financing for Islamic Commercial Banks for the 2018-2021 Period.